Rediscovery of a poorly known Chinese stonefly, Flavoperla ovalolobata (Wu, 1948) (Plecoptera: Perlidae) - Liu, Hao; Yan, Yanhua; Li, Weihai; Shi, Mingwang (Zootaxa, 2020)
A poorly known perlid species, Flavoperla ovalolobata (Wu, 1948) is redescribed based on an adult male and four females newly collected at the type locality, Wuyishan located in Fujian Province of southeastern coastal China. Illustrations and color photographs are provided for this species. The taxonomic relationship of this taxon is discussed with related taxa.